INDIAN TRIBAL WELFARE SCHEMES AND THEIR IMPLEMENTATION: A STUDY - Dr. Basavaraj Bheemaraya, (EPRA International Journal of Economic and Business Review(JEBR), 2022)
India has the largest concentration of tribal people anywhere in the world except perhaps in Africa. The tribal’s are children of nature and their lifestyle is conditioned by the eco‐system. India with a variety of eco-systems presents a varied tribal population throughout its length and breadth. Moreover the tribal development schemes have not brought any changes in the life of majority of the tribal people .Inclusive growth is not making the fruits of development available and accessible to the tribal population of India. The present research paper is confined to the origin and theoretical background of Tribal Welfare and to evaluate the tribal development planning, and important eyesight to tribal development in India, particularly in Karnataka. The paper also highlights development of Tribal in India during five year planning period. The Government of India as provide more number of schemes, Welfare facilities and Programmes for the motive to development of Tribal people in India.